SELF-EFFICACY AND EMOTIONAL INTELLIGENCE AS PREDICTORS OF ADMINISTRATIVE EFFECTIVENESS IN SECONDARY SCHOOLS - Ahmed, Hassan Taiye; Lasisi, Kamil Adekola; Abdulkareem, Habibat Bolanle (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
The study examined self-efficacy and emotional intelligence as predictors of administrative effectiveness in secondary schools in Ilorin metropolis. Descriptive survey research design of the co relational type was adopted. The sample was 100 male and female respondents which include 20 secondary school principals and 80 vice principals. A purposive sampling was used to select 4 Local Government .Stratify sampling was used to classify Schools into rural, urban and semi-urban. Availability sampling techniques was used to administer the instruments to the principals and vice. Principal self-efficacy by Smith, Strom, Adams (2019) and Emotional Intelligence Scale (EIS) with 0.75 reliability coefficient. Frequency and percentage was used to present demographic data and Pearson Product Moment Correlation Coefficient (PPMC) at 0.05 level of significance. The study found that there is a significant relationship between self-efficacy and administrative effectiveness of principals (r.cal. = 0.431, P0.05). The study found that there is a significant relationship between emotional intelligence and administrative effectiveness of principals (r.cal. = 0.210, P0.05). The study concludes that there is significant difference in the self-efficacy, emotional intelligence to the administrative effectiveness of principals .There is significant difference in the self-efficacy, emotional intelligence to the administrative effectiveness of male principals and there is significant difference in the self-efficacy, emotional intelligence to the administrative effectiveness of female principals.